The impact of health status and smoking behaviour on Indonesian labor wage - Heni Wahyuni (Universitas Islam Indonesia, 2016)
In this research, we try to estimate the relationship between health status and smoking behaviour on the labour wage in Indonesia. We investigate using Indonesian Family Life Survey (IFLS) data and two-step Heckman correction to deal with sample selection bias. We found that there is significance relationships between all socioeconomic variables and wage both for smokers and non-smokers. The interesting thing is that the effect on wage is less for smokers than non-smokers.